Modeling and Analysis of a Diaphragm Micropump with Annular Actuation Using Bond Graphs - Uma B. Baliga; Ranjith R.G.; S.M. Kulkarni (International Journal of Machine Systems and Manufacturing Technology, 2024)
Micropumps have been around for a while and are utilized for many things, including electrical cooling and biomedical applications. Numerous researchers have experimented with varying the chamber, diaphragm, pumping mechanism, or actuation mechanism materials to improve the device's performance. Despite this, the micropumps employed in the practical applications mentioned above fall short of meeting the necessary flow rates and pressure. In this study, annular actuation is proposed to enhance performance. The bond graph technique models the pump and calculates the flow rate and pressure output. The results show that annular actuation results in more significant diaphragm deflection, and thus, a flow rate of 3000 ml/h is 62% more than the conventional central actuation.
Keywords: Micropump; annular actuation; bond graph; deflection; diaphragm